THE BIBLE IN THE STRUCTURE OF N. S. LESKOV'S “THE SINGLETHOUGHT” - Marta Lukashevich (Проблемы исторической поэтики, 2012)
There are a lot of facts to prove that Nikolai Leskov placed great emphasis on the Bible in his career as a writer. His earlies contributions to newspapers were devoted to the issue of the Bible's accessibility. As a publisher and editor, he did a lot to improve the knowledge of the Bible among the Russian people, viewing this process as a basis for moral education. Leskov's works of fiction often feature biblical quotes, reminiscences and imagery. The objective of our article is to assess the importance of the Bible for the structure of Odnodum (The Singlethought) - a short story Leskov wrote in 1879. Set against other texts of the same author, The Singlethought stands out as a text where the link to the Bible is more accentuated both in form and content. We provide an analysis of how the Bible influenced the personality growth of the protagonist, Alexander Ryzhov, and his behavior models, as well as how the society views him. It is also important to provide the historical context of the discussions of the role of the Bible in the life of the Orthodox community, namely the debates on the Russian Bible Society and the Russian translation of the Bible. Ryzhov's reputation of “an eccentric” and “of doubtful faith” put him in the same class with Leskov's other righteous characters, making this protagonist timeless and important.